2000
DOI: 10.1291/hypres.23.303
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Activity and Body Mass Index Contribute to Blood Pressure Levels.

Abstract: Toshio 0 GIHARA, The purpose of this study was to clarify the relationships between obesity (BMI) and BP levels, leptin levels, sympathetic activity, and insulin sensitivity in a Japanese male population. In 912 young, non-diabetic, Japanese men with a wide range of BMI (16.5-33.6 kg/m2), blood pressure (BP), fasting plasma norepinephrine (NE), insulin and leptin levels were measured after an overnight fast. The cohort consisted of 603 normotensive and 309 hypertensive subjects. The study was carried out using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 40 publications
2
47
0
1
Order By: Relevance
“…53 Some studies have also suggested that overeating and subsequent weight gain is responsible for sympathetic overactivity, 53,54 whereas others have shown that sympathetic overactivity might lead to excess weight. 20,55 In conclusion, this study indicates that a substantial proportion of young university adults indicated obesity, hypertension and tachycardia. We also show that the degree of adiposity (BMI) indicated significant and independent relationships with SBP, DBP and resting HR, but of the three cardiovascular variables, SBP indicated the strongest association with BMI in both genders.…”
Section: Discussionmentioning
confidence: 54%
“…53 Some studies have also suggested that overeating and subsequent weight gain is responsible for sympathetic overactivity, 53,54 whereas others have shown that sympathetic overactivity might lead to excess weight. 20,55 In conclusion, this study indicates that a substantial proportion of young university adults indicated obesity, hypertension and tachycardia. We also show that the degree of adiposity (BMI) indicated significant and independent relationships with SBP, DBP and resting HR, but of the three cardiovascular variables, SBP indicated the strongest association with BMI in both genders.…”
Section: Discussionmentioning
confidence: 54%
“…This finding, together with those previous reports that the systemic renin-angiotensin system is activated by HF feeding, 22 suggests that AngII may contribute to the upregulation of catecholamine biosynthetic enzymes in the adrenal medulla, and to the elevated plasma catecholamine levels observed in obese subjects. 39 In conclusion, this study shows that feeding obesity-prone SpragueDawley rats with a 60% HF diet for 24 weeks results in elevated BP, reduced daytime HR dipping and delayed cardiovascular post-stress recovery. In addition, HF diet feeding upregulates AT 1 receptors and NADPH oxidase subunits in the hypothalamus with a concomitant increase in NADPH oxidase-dependent superoxide production, possibly leading to superoxide-mediated sympathoexcitation and hypertension.…”
Section: Discussionmentioning
confidence: 58%
“…The association between norepinephrine and obesity is supported by our results and by previous studies in young people demonstrating that elevated plasma norepinephrine levels increase with the increase in BMI predicting the development of hypertension. 25 Moreover, subjects with a family history of obesity have been shown to be characterized by higher plasma norepinephrine and BP levels. 26 In the present study, subjects with daytime SH had higher urinary epinephrine levels, suggesting that adrenal medulla and peripheral sympathetic nervous system hyperactivities are associated with early BP elevations.…”
Section: Discussionmentioning
confidence: 99%